Impact of construction activities towards community / Nur Athirah Mohd Rosli and Mohamad Tajudin Saidin - Mohd Rosli, Nur Athirah; Saidin, Mohamad Tajudin (2019)
A construction project involves a lot of physical activities. The Government has urged to professional bodies and developers to take proactive actions to promote the sustainability concept within their domain and be responsive to the need for better environmental and social protection. However, a construction project can give benefits and harms directly or indirect not only to the country but also to the neighborhood as well. The aim of this research is to determine the impacts of construction project towards neighborhood in the urban area. The objective of the research is to identify the impacts of the construction project on the community surrounding the construction site. To achieve this, the questionnaires were distributed to the community around the construction site at Kota Bharu, Kelantan. A total of 84 out of 100 respondents have returned their responses by completing all the questionnaires. The data will be analysed in the form of descriptive analysis by using the latest version of SPSS. It is found that impacts can be divided into three; environmental impact, social impact, and economy impacts. However, the economy gives the greatest impact to the neighborhood. The result of this study is beneficial for the construction managers and other parties involve in the construction site to become aware of the construction activities.